1975
DOI: 10.1093/brain/98.2.317
|View full text |Cite
|
Sign up to set email alerts
|

Simple Reaction Time: Evidence for Focal Impairment From Lesions of the Right Hemisphere

Abstract: Simple reaction time is significantly increased in patients with unilateral lesions of either cerebral hemisphere responding with the hand ipsilateral to the lesion, but the effect is much greater when the lesion is in the non-dominant hemisphere. This difference cannot be attributed to asymmetries in the size or type of lesion. It applies over the complete distribution of reaction times as well as to the means, and is not diminished by practice. Neither the classical conduction model of reaction time nor the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1
7

Year Published

1977
1977
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(64 citation statements)
references
References 0 publications
6
50
1
7
Order By: Relevance
“…Neglect patients' attention for right targets seemed thus enhanced with respect to RBD control patients, consistent with the opponent processor model. As La Ádavas et al [95] pointed out, according to this model neglect patients should be faster for right-sided stimuli even with respect to normal individuals without brain damage; this, however, would be an unlikely result, given that right brain lesions cause a de®cit in arousal [96]. Indeed, subsequent RT studies [97±101] invariably found that left neglect patients were slower than normal controls when responding to right (ipsilesional) stimuli (Fig.…”
Section: A Rightward Attentional Bias In Left Neglectmentioning
confidence: 91%
See 2 more Smart Citations
“…Neglect patients' attention for right targets seemed thus enhanced with respect to RBD control patients, consistent with the opponent processor model. As La Ádavas et al [95] pointed out, according to this model neglect patients should be faster for right-sided stimuli even with respect to normal individuals without brain damage; this, however, would be an unlikely result, given that right brain lesions cause a de®cit in arousal [96]. Indeed, subsequent RT studies [97±101] invariably found that left neglect patients were slower than normal controls when responding to right (ipsilesional) stimuli (Fig.…”
Section: A Rightward Attentional Bias In Left Neglectmentioning
confidence: 91%
“…Another component of attention, arousal, might be disrupted more by right than by left-hemisphere lesions [96,141]. Since, as we have seen, an arousal de®cit seems to contribute to neglect behavior [75,102,139], this could be another basis for the asymmetry of occurrence of neglect after unilateral brain lesions [56,142].…”
Section: Impaired Exogenous Orienting In Unilateral Neglect: Implicatmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, Howes and Boller (1975), examining maps of the brain scan for patients with the slow reaction times to simple auditory stimulus, have suggested that structures in or near the basal ganglia and the posterior parietal region of the right hemisphere are critical for the lengthened reaction time. In the present study, however, there was no significant difference of PMTs between the normal and the Parkinsonian subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Such emotional dominance logically follows from the right hemisphere dominance for regulating bilateral cortical arousal levels (Howes & Boller, 1975;Green & Hamilton, 1976;Heilman, Schwartz, & Watson, 1978;Heilman & Van Den Abel, 1979;Heller, 1993), as any intense emotion requires arousal or activation. Sympathetic reactions to emotional events are also associated with right hemisphere activation (Wittling, 1990;1997), which is said to be the primary anatomical location for emotional comprehension and emotional expression (Heilman, 1997).…”
Section: -Right Hemisphere Model Of Emotionmentioning
confidence: 99%